An Observational Clinical Study on Efficacy of Brahmi Ghrita Nasya in Anidra (Insomnia) Irrespective of Disease Condition. - Bhatt, Chintan J; Patel, Kalapi B (International Research Journal of Ayurveda & Yoga, 2024)
Insomnia is the most common sleep related complaint with the prevalence of 10%-48% in general population. Charaka Samhita has considered Nidra as one of the Trayopasthambha which indicates the importance of the Nidra. Aswapna is Vataja Nanatmaja Vikaras. Anxiety is one of the most common causes of insomnia which is observed commonly in the patients having chronic illnesses. Susruta samhita and Charaka Samhita also mention mental distress and physical disorders as causes of Anidra. Brahmi ghrita is used in the treatment of mental disorders. Hence Brahmighrita is used for the Nasya in the patients complaining Anidra in P.D. Patel Ayurved Hospital, Nadiad. The main aim of study is to evaluate the effect of Brahmi Ghrita Nasya in Anidra (insomnia) irrespective of disease condition. Considering role of Manas in Anidra; Nasya with Brahmighritais preferred because of its Medhya property